Organization of the ventricular zone of the cerebellum - Gómez-González, Gabriela B.; Becerra-González, Marymar; Martínez-Mendoza, Marianne Lizeth; Rodríguez-Arzate, Cynthia Alejandra; Martínez-Torres, Ataúlfo (Frontiers in Cellular Neuroscience, 2022)
The roof of the fourth ventricle (4V) is located on the ventral part of the cerebellum, a region with abundant vascularization and cell heterogeneity that includes tanycyte-like cells that define a peculiar glial niche known as ventromedial cord. This cord is composed of a group of biciliated cells that run along the midline, contacting the ventricular lumen and the subventricular zone. Although the complex morphology of the glial cells composing the cord resembles to tanycytes, cells which are known for its proliferative capacity, scarce or non-proliferative activity has been evidenced in this area. The subventricular zone of the cerebellum includes astrocytes, oligodendrocytes, and neurons whose function has not been extensively studied. This review describes to some extent the phenotypic, morphological, and functional characteristics of the cells that integrate the roof of the 4V, primarily from rodent brains.